Our skin : a first conversation about race - Madison, Megan; Ralli, Jessica (Madison, Megan. First conversations., 2021)
"An age-appropriate introduction to the concepts of race, gender, consent and body positivity, developed by early childhood and activism experts, combines clear text with engaging artwork to help the youngest children recognize and confront unjust actions."--